Visibly Queer- and Trans-Fashion Brands and Retailers in the Twenty-First Century: The Production and Distribution of Binders, Packers, Underwear, Lingerie, and Bras. (2nd January 2022) - Reddy-Best, Kelly L.; Streck, Kyra; Farley Gordon, Jennifer
Abstract : Socially conscious fashion entrepreneurs in the twenty-first century built many of the first visibly queer- and trans-focused fashion brands. In this paper, we critically examine nine of these brands that produced and distributed undergarments or other objects worn near or against the skin, such as binders, packers, underwear, lingerie, and bras. We draw upon oral histories with the brand directors, objects from each company, news articles, and online content. The brands emerged during significant socio-cultural and political changes and simultaneously engaged in dismantling and queering the past oppressive notions of the fashion industry. Unlike mainstream representation that often has positioned fashionable queer people as thin, cisgender, and white, these brands embraced an intersectional and social-justice lens throughout their business processes. The history of these brands demonstrates the interconnected complexity of fashioning queer and trans identities, fashion commodities, and fashion activist philosophies in the twenty-first-century capitalist marketplace.